Exploring the maternal and infant continuum – ethnic disparities in infant hospital admissions for respiratory disease. (30th March 2016) - Lawton, Beverley; Stanley, James; Filoche, Sara; Garrett, Sue; Rose, Sally B.; Robson, Bridget; Elley, C. Raina
Abstract: Objective: To investigate maternal and birth‐related risk factors associated with infant respiratory hospitalisations in New Zealand. Methods: A Kaupapa Māori‐framed retrospective cohort analysis of public hospital maternal data linked to infant data (54, 980 births 1995–2009). Primary outcome was rate of hospitalisation for respiratory disease in the first year of life. Risk variables examined included socioeconomic status (SES), age, smoking, parity, gestation, time to hospital discharge, breastfeeding and maternal ethnicity as a potential marker of differential exposure to risk factors. Results: Independent risk factors for hospitalisation included low maternal SES (rate ratio: 1.33 [95% CI 1.19–1.49]); smoking (1.3 [1.19–1.41]); parity (2.77 [2.37–3.24]); preterm birth (3.14 [2.58–3.83]; 30 compared with 40 weeks); but not breastfeeding (0.99 [0.87–1.11]). After adjustment for risk factors, respiratory hospitalisations remained highest among infants of young Māori women (rate ratio 1.93 [1.46–2.55] at age 22.5 years) and Pacific women across all maternal age groups (rate ratios 2.43 to 2.55), compared with infants of European women. Conclusions: Maternal and birth factors are strongly associated with ethnic disparities in infant hospital admissions for respiratory disease. Implications: Interventions that begin in pregnancy and address risk factors and social determinants of health are needed to address these disparities.